Fertility intentions and maternal health behaviour during and after pregnancy. (2nd January 2020) - Chatterjee, Esha; Sennott, Christie
Abstract : This study examines associations between fertility intentions and maternal health behaviours during and after pregnancy among a nationally representative sample of 3, 442 women from India. Two waves of data (2005, 2012) from the India Human Development Survey were analyzed to investigate the influence of unwanted births on women's use of antenatal care, timely postnatal care, and the delivery setting using binary and ordered logistic regression, partial proportional odds models, and propensity score weighting. Fifty-eight per cent of sample births were unwanted. Regression results show that, net of maternal and household characteristics, women with unwanted births were less likely to obtain any antenatal care and had fewer antenatal tests performed. Unwantedness was also associated with a lower likelihood of delivering in an institutional setting and of obtaining timely postnatal care. The relationships between unwantedness and antenatal care, postnatal care, and delivery setting were robust to models accounting for propensity weighting.